Shift formal regulations on Mesopotamian pottery (Pottery Samarra model): محمد جاسم محمد العبيدي (Al-Academy, 2016)
Operated Alandziahih "drift theory" as a science talk in most of the cash and technical studies in the early twentieth century, making him and the sciences, arts and culture both fields of experiences, in an attempt to explore the institutions that theory, a number of laws which took control in the internal structures of those acts, resulting in for those institutions to be actively contribute their ideas to guide the pace on the right track. And thus lay the foundations of this theory, which was a big affair in the early twentieth century and still vigorous pace to this day, particularly their applications in various fields of the arts.Although each type of Arts, both in the composition or the theater or means of communication, took join the structure theory for you draw the structure and internal systems according to their own rules, but the modernity and beyond the weakening of the boundaries between the different arts races of non-premeditated, which I took the theoretical drawing new forms and institutions of helpfulness for change theory to the normal function of those technical races, which we have created that this theory is that the response to changes in the various arts structures, and this theory structures are pottery arts, and testing operations for that vocabulary for various Arts, from its beginnings and to the present time, whether mural paintings in caves, or pottery or sculptural works up to the architecture, and in response to developments of the changes caused by drift can adapt the artwork of any kind ((pottery, sculpture, mural)) and the process of recovery to those arts, and the process of expanding to accommodate those mechanisms theory and its applications on the pottery arts. And has managed the artist pottery to paint a model of the new theory, mechanisms and make use of its data, which annihilate the spirit of the artwork, and bear fruit from her tree, especially summon all that is old, towards the contemporary, and its we can achieve a kind of chaos, even the limits of control character Alanziahi on the artwork, which Taking captures those mechanisms by employing legibility, especially ancient pottery arts and everything that has a poetic performance of up to naivete and simplicity in technical her performances